Biphotonic Ionization of DNA: From Model Studies to Cell1. (28th November 2018) - Cadet, Jean; Wagner, J. Richard; Angelov, Dimitar
Abstract: Oxidation reactions triggered by low‐intensity UV photons represent a minor contribution with respect to the overwhelming pyrimidine base dimerization in both isolated and cellular DNA. The situation is totally different when DNA is exposed to high‐intensity UVC radiation under conditions where biphotonic ionization of the four main purine and pyrimidine bases becomes predominant at the expense of singlet excitation processes. The present review article provides a critical survey of the main chemical reactions of the base radical cations thus generated by one‐electron oxidation of nucleic acids in model systems and cells. These include oxidation of the bases with the predominant formation of 8‐oxo‐7, 8‐dihydroguanine as the result of preferential hole transfer to guanine bases that act as sinks in isolated and cellular DNA. In addition to hydration, other nucleophilic addition reactions involving the guanine radical cation give rise to intra‐ and interstrand cross‐links together with DNA–protein cross‐links. Information is provided on the utilization of high‐intensity UV laser pulses as molecular biology tools for studying DNA conformational features, nucleic acid–protein interactions and nucleic acid reactivity through DNA–protein cross‐links and DNA footprinting experiments. Abstract : Main reactions of the guanine radical cation ( G · + ) in isolated and cellular DNA upon either direct biphotonic ionization or hole transfer from other purine and pyrimidine radical cations to guanine. (a) Deprotonation pathway. (b) Hydration pathway. (c) Other nucleophilic reactions.